(untitled) (Bioscience Journal, 2019)
Functional foods are those that, beyond basic nutrition, promote health benefits. This study aimed to produce a fermented beverage from a water-soluble soybean extract and low-lactose semi-skimmed milk. The beverage was prepared using a blend (v/v) containing 62% water-soluble soybean extract, 33% low-lactose semi-skimmed milk, and 5% of an inoculum containing Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus salivarius subsp. thermophilus. The fermentation was carried out with monitoring of the lactic acid bacteria (LAB) counts, pH, and titrable acidity (% lactic acid). The consumption-ready fermented beverage was added of strawberry syrup and posteriorly characterized by its centesimal composition and sensory attributes as appearance, aroma, flavour, texture, overall impression, and purchase intent. Additionally, the LAB count and presence of pathogens in the final product were evaluated. After 14 h of fermentation, the refrigerated product presented L. bulgaricus and S. thermophilus counts of 8.5 × 103 and 7.4 × 107 CFU/mL, respectively. The product contained 14.93% carbohydrates, 0.76% fats, 0.96% ash, 22.76% total solids, and 2.19% protein. Because the product did not present any pathogens, it was adequate according to the standards of microbiological safety determined by Brazilian legislation. Regarding the sensory evaluation, the panelists assigned a mean score of 7.0 for the attributes evaluated, indicating ‘liked moderately’ to the drink. In addition, 61% of the evaluators responded that they ‘certainly or probably would buy’ the product if it were available on the market.